Evaluation of Iron Supplier Selection at PT. XYZ uses Analytical Network Process (ANP) method and Technique for others preference by Similarity to Ideal Solution (TOPSIS) - Amarullah, Rafid (Journal of Optimization System and Ergonomy Implementation, 2024)
PT. XYZ is one of the developer companies Property. In this study, the Analytical method was used Network Process (ANP) and Technique For Others methods Preferences by Similarity to Ideal Solution (TOPSIS) in Respond to supplier evaluation problems that occur in company. Based on the results of the study, it was obtained the ranking of each criterion. On the price criterion consists of H1 (0.262), H4 (0.261), H5 (0.244), and H2 (0.233). At quality criteria consist of K3 (0.384), K4 (0.377